2017
DOI: 10.2135/cropsci2016.07.0623
|View full text |Cite
|
Sign up to set email alerts
|

Multisplit Nitrogen Application via Drip Irrigation Improves Maize Grain Yield and Nitrogen Use Efficiency

Abstract: Conventional fertilization with most N applied before or during early maize (Zea mays L.) growth stages can negatively affect production if soil N is insufficient after silking. Here, drip irrigation with a split application of N (drip fertigation) was evaluated to determine whether the effect on yield and N use efficiency (NUE) differs with cropping practice. Compared with conventional fertilization, drip fertigation increased yield by 13 and 14% at a low planting density under a low N rate (L) and by 15% at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 69 publications
2
25
0
Order By: Relevance
“…Leaf expansion increased the storage capacity of N in leaves and promoted carbon supply to the stalk, resulting in high maize production [34]. Our research showed that the variation in dry matter under different N rates was a result of differences in plant height, which had significant linear relationships with dry matter [35]. On the other hand, N2 and N3 increased LAI and chlorophyll contents, which led to greater accumulation of photosynthate, and eventually, promoting an increase in dry matter [33].…”
Section: Discussionmentioning
confidence: 64%
“…Leaf expansion increased the storage capacity of N in leaves and promoted carbon supply to the stalk, resulting in high maize production [34]. Our research showed that the variation in dry matter under different N rates was a result of differences in plant height, which had significant linear relationships with dry matter [35]. On the other hand, N2 and N3 increased LAI and chlorophyll contents, which led to greater accumulation of photosynthate, and eventually, promoting an increase in dry matter [33].…”
Section: Discussionmentioning
confidence: 64%
“…Recommendations for the appropriate timings of N application to improve crop NUE has dated back to the previous century (Matson et al, 1998 ). Compared with applying all N fertilizer prior to sowing, splitting and delaying N application may improve both maize NUE and grain yield (Zhou et al, 2017 ). Qwing to the reduced N uptake with the ethephon treatment, there may be plenty of N left in the soil, which may increase the leakage and waste of N fertilizer.…”
Section: Discussionmentioning
confidence: 99%
“…Replacing chemical fertilizer with organic fertilizer can effectively avoid soil acidi cation and improve soil nutrient contents and soil enzyme activities (Okami et al, 2016). Fertilization by stages can signi cantly improve the fertilizer utilization rate and increase crop yield (Zhou et al, 2017). The combined application of organic and inorganic fertilizers can not only increase wheat yield but also improve soil physical and chemical properties and signi cantly enhance nitrogen fertilizer use e ciency (Xia et al, 2017;Zhao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%